Contrasting patterns of carbon sequestration between Gilbertiodendron dewevrei monodominant forests and Scorodophloeus zenkeri mixed forests in the Central Congo basin - Cassart, Benoît; Basia, Albert Angbonga; Titeux, Hugues; Andivia, Enrique; Ponette, Quentin (Plant and soil, 2017)
Aims Gilbertiodendron dewevrei (De Wild.) J. Léonard monodominant forests (MOF) and Scorodophloeus zenkeri Harms mixed forests (MIF) frequently co-occur on similar soil conditions in the Central Congo basin. Although tree species composition is known to impact C storage, the patterns of C sequestration between those contrasted forest types as well as the associated drivers remain unknown. Methods Annual litterfall, as well as soil (forest floor and mineral soil down to 220 cm depth) organic C (SOC) and aboveground C (AGC) stocks were investigated in MIF and MOF located on highly weathered sandy soils in the Yoko Reserve (DRC). Results The annual leaf litterfall was similar under both forests but litterfall quality in MOF strongly differed by a set of traits related to organic matter recalcitrance. The SOC stock down to 220 cm was 55% higher under MOF compared to MIF, and the differences between forests remained significant down to 100 cm. While the combined SOC and AGC stocks were similar in both forests, the SOC stocks accounted for ca. 19 and 33% of the total C stocks in MIF and MOF, respectively. Conclusions Because of similar litterfall C inputs, we conclude that the greater SOC accumulation under G. dewevrei results from a limitation of the decomposition rate, in agreement with the traits of the corresponding leaf litter.